CLA for More Effective Development Programs (video) (USAID, 2014)
This presentation features USAID/PPL's Stacey Young discussing the history of learning at USAID; how collaborating, learning, and adapting (CLA) can enhance development outcomes, and the role of implementing partners in supporting this vision.